Jawapan

  • Pengguna Brainly
2016-01-24T21:37:45+08:00
F (x) = 5x , g (x) = 4x + 3
 
fg ( x ) = f ( g(x) )
            = f ( 4x + 3 )
            = 5 ( 4x + 3 )
            = 20x + 15

gf (x) = g ( f(x) )
          = g ( 5x )
          = 4 ( 5x ) + 3
          = 20x + 3

f^2 (x) = f ( f(x) )
           = f ( 5x )
           = 5 ( 5x )
           = 25x

g^2 (x) = g ( g(x) )
            = g ( 4x + 3 )
            = 4 ( 4x + 3 ) + 3
            = 16x + 12 + 3
            = 16x + 15
2 5 2
Sbnarnya soalan ni bleh dirujuk di bku teks m/s 16 soalan 1
saya sa abis sklh...